How new is the New Testament? : First-Century Judaism and the emergence of Christianity - Hagner, Donald Alfred (Baker Academioc; Grand Rapids., 2018)
"A senior New Testament scholar tackles the issue of how distinct early Christianity is from the formative Judaism from which it emerged"--
The question of continuity and discontinuity -- The Gospels of Mark and Matthew -- The Gospel of Luke -- The Acts of the Apostles -- The Gospel of John and the Johannine letters -- The Pauline corpus -- Hebrews and the Catholic letters -- The Apocalypse -- Newness in the New Testament : continuity and discontinuity.
Includes bibliographical references (pages 181-195) and indexes.
Keywords: Bible. -- History; Church history -- Primitive and early church, ca. 30-600.; Judaism -- Relations -- Christianity -- History; Christianity and other religions -- Judaism; Christianity -- Origin